Communicating partners : 30 years of building responsive relationships with late-talking children including autism, Asperger's syndrome (ASD), Down syndrome, and typical development developmental guides for professionals and parents /: 30 years of building responsive relationships with late-talking children including autism, Asperger's syndrome (ASD), Down syndrome, and typical development developmental guides for professionals and parents. (©2004) - Unknown
No abstract available